FIRM SIZE, GROWTH, MEDIA EXPOSURE DAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR - Ni Wayan Sri Rahayu Darmayanti; Anak Agung Ngurah Oka Suryadinatha Gorda (Universitas Pendidikan Nasional, 2018)
Firm Size, Growth, Media Exposure and Corporate Social Responsibility of Manufacturing Companies. This study aims to determine the effect of Firm Size, Growth, Media Exposure and Corporate Social Responsibility on Manufacturing Companies listed on the Indonesia Stock Exchange in 2015-2017. The sample selection uses purposive sampling, which is as many as 100 samples of manufacturing companies. To measure the hypothesis is done by t test and f test. The data analysis technique used in this study is the classic assumtion test and multiple linear regression test. In addition, all variables are declared free of interference from existing classical assumptions. From the results of multiple linear regression tests the results of the f test are 78.906 with a significant value of 0.000 or <0.05. This means Firm Size, Growth and Media Exposure to Corporate Social Responsibility in Manufacturing Companies listed on the Indonesia Stock Exchange in 2015-2017 have a significant simultaneous effect. Partial testing shows that all independent variables have a significant effect on Corporate Social Responsibility.Keywords: Firm Size, Growth, Media Exposure, Corporate Social Reponsibility